Peran Implementasi Modal Intelektual terhadap Peningkatan Keberlanjutan Kemajuan Usaha Mikro Kecil Menengah (UMKM) di Kabupaten Sumbawa - Abdul Salam; Serli Oktapiani; Jayanti Mandasari (Owner : Riset dan Jurnal Akuntansi, 2023)
This study aims to examine the influence of Human Capital, Capital Structure, Relational Capital on Increasing the Sustainability of the Progress of MSMEs in Sumbawa Regency. This research uses quantitative methods. The population in this study are MSME actors in Sumbawa Regency, with a total sample of 270 respondents using purposive sampling techniques. The data collection method used was by distributing questionnaires directly to respondents and then processing them using the Multiple Linear Regression analysis tool with SPSS. The results of this study show that Human Capital, Structural Capital, Relational Capital have an effect on Increasing the Sustainability of MSME Progress in Sumbawa Regency.